Propuesta de reforma legal al libro segundo, titulo ii, sección iv-a del código de comercio, relacionado a la venta con reserva de dominio - Nuñez Puetate, Byron Josè (2014)
The National Assembly, in its duty to make laws, including those aimed at compliance and protection of trade between the citizens of the country has forgotten reform, repeal, or add items to enable safeguard the rights of those who for one reason or another buy or sell goods in the form prescribed in the law, one of these is the purchase of goods, leaving the ownership of the thing to the creditor until the buyer makes full payment of the same. If we take into account that trade from its beginnings in the world, led to the development of societies and creating a system that allows human beings to make objects or personal property in order to offer them in the market and sell them to the highest bidder, using mechanisms have been established and refined, in order to implement such mechanisms for the benefit of those involved in these negotiations. It is so with the passing of the years through history trade has gone technifying and created new methods and procedures, in order to sell a good or service, this with the intention of benefiting both the buyer and seller. It is for this reason that human beings in their desire to continue to evolve in the commercial field established within commercial laws, ones that will allow the buyer to purchase a chattel, with a very affordable payment mode, this is the payment funded or deadlines to allow for a certain time to acquire full control of chattel. One of these ways is the sale with reservation of ownership, as already indicated at the beginning allows the seller to retain the ownership of the thing sold until full payment of the same, but giving the buyer the right to use and benefit from the when the transaction is executed. The problem of the sale with reservation of ownership is visible because there is no appropriate legislation, as is visible improper justice system, which should be provided and assume an appropriate legal framework to ensure due process, and legal certainty to the parties involved in such disputes.